Voices from the Digital Classroom 25 Interviews about Teaching and Learning in the Face of a Global Pandemic - Abegglen, Sandra; Neuhaus, Fabian; Wilson, Kylie (University of Calgary Press, 2022)
The sudden shift to remote education in response to the COVID-19 pandemic created both a unique challenge and a unique opportunity. Students and instructors alike were required to quickly adapt to the digital classroom, adjusting methods, material, and pedagogical approaches on the fly. Bringing together twenty-five interviews from the frontline of emergency remote education, Voices from the Digital Classroom portrays the struggles, innovations, and resilience of students, instructors, and educational professionals in the face of COVID-19. These interviews offer a unique, of-the-moment perspective on an exceptional time. Complemented by additional voices that expand on stories told to reflect on challenges, successes, and lessons learned,Voices from the Digital Classroom is both a time-capsule and a vision for the future. It provides new insights into pandemic teaching and learning, a remarkable lens into the daily realities of the digital classroom, and an inspiration for the future of remote education in a post-pandemic world.